Prognostic implications of and clinical risk factors for acute lung injury and organizing pneumonia after lung transplantation: Data from a multicenter prospective cohort study. Issue 12 (12th September 2022) - Pavlisko, Elizabeth N.; Neely, Megan L.; Kopetskie, Heather; Hwang, David M.; Farver, Carol F.; Wallace, W. Dean; Arrossi, Andrea; Illei, Peter; Sever, Michelle L.; Kirchner, Jerry; Frankel, Courtney W.; Snyder, Laurie D.; et al.
Abstract : We determined prognostic implications of acute lung injury (ALI) and organizing pneumonia (OP), including timing relative to transplantation, in a multicenter lung recipient cohort. We sought to understand clinical risks that contribute to development of ALI/OP. We analyzed prospective, histologic diagnoses of ALI and OP in 4786 lung biopsies from 803 adult lung recipients. Univariable Cox regression was used to evaluate the impact of early (≤90 days) or late (>90 days) posttransplant ALI or OP on risk for chronic lung allograft dysfunction (CLAD) or death/retransplantation. These analyses demonstrated late ALI/OP conferred a two‐ to threefold increase in the hazards of CLAD or death/retransplantation; there was no association between early ALI/OP and these outcomes. To determine risk factors for late ALI/OP, we used univariable Cox models considering donor/recipient characteristics and posttransplant events as candidate risks. Grade 3 primary graft dysfunction, higher degree of donor/recipient human leukocyte antigen mismatch, bacterial or viral respiratory infection, and an early ALI/OP event were significantly associated with increased late ALI/OP risk. These data from a contemporary, multicenter cohort underscore the prognostic implications of ALI/OP on lung recipient outcomes, clarify the importance of the timing of these events, and identify clinical risks to target for ALI/OP prevention. Abstract : Data from a multi‐center prospective cohort shows that the development of late, defined as more than 90 days after transplantation, but not early acute lung injury or organizing pneumonia confer worse outcomes for recipients.